Analysis and Testing of MR Shear Transmission Driven by SMA Spring. (25th September 2013) - Huang, Jin; Chen, Xu; Zhong, Lirong
Abstract : A transmission method of magnetorheological (MR) fluid in cylindrical-type driven by shape memory alloy (SMA) spring with the thermal effect was proposed. The torque can change rapidly with temperature. Based on the thermal effect of SMA, the expression for displacement of SMA spring was established. The rheological property of MR fluid under the magnetic fields was described by Bingham model. Based on momentum equation, the shear flow of MR fluid between two cylinders was analyzed and the expressions of flow velocity and torque have been obtained. The experimental results show the output displacement of SMA spring and the transmit torque of MR fluid is directly proportional to the temperature and the applied magnetic field, respectively.